Should etomidate be the induction agent of choice in the emergency department? - Netshandama, Betty (University of Limpopo (Medunsa Campus), 2014)
Purpose: The purpose of this study was to determine whether etomidate should be the induction agent of choice for Rapid Sequence Intubation in the Emergency department due to its haemodynamic stability. Objective: To measure the haemodynamic effects of etomidate post- induction in patients undergoing Rapid sequence intubation. Methods: This was a prospective, randomized, observational and unblinded study. The study was conducted at DR GEORGE MUKHARI HOSPITAL theatre unit on 45 patients between the ages of 11 and 65 years of age who fall under the American Society of Anaesthesiology classification (ASA) IE – IIIE. Each patient had an established intravenous line, was pre-oxygenated and then received etomidate (0.2 mg – 0.3 mg/kg). Cricoid pressure was applied immediately following loss of consciousness. Suxamethonium 1.5 mg/kg or Rocuronium 1.2 mg/kg was administered and this was followed by endotracheal intubation 60 seconds later. Data collected included amongst others vital signs:- Heart Rate, Systolic Blood Pressure, Diastolic Blood Pressure and Mean Arterial Pressure which were measured pre-induction, immediately post-intubation, 2.5 minutes, 5 minutes and 7.5 minutes later by a non invasive automated blood pressure monitor. Statistical Analysis: Descriptive statistical analysis was applied using the SPSS (Statistical Programme for Social Sciences) to demonstrate the demographics and ASA classifications of the patients in the study. Mean standard deviations were calculated for both males and 10 females in the study. Changes in vital signs immediately post-intubation were graphically demonstrated. The changes in vital signs (HR, SBP, DBP and MAP) were calculated and differences in such changes over-time were expressed as p-value. Significant differences in changes of the vital signs were noted if p ≤ 0.05. Results: The blood pressure increased immediately following intubation due to laryngoscopy and intubation. As anaesthesia progressed (i.e. 2.5 minutes, 5 minutes and 7.5 minutes later) the blood pressure gradually declined to levels lower than pre-induction values but at acceptable levels. Conclusion: Etomidate is an effective anaesthetic induction agent as it is haemody-namically stable and thus should be used in an Emergency department
Thesis (M Med (Anaesthesiology)) -- University of Limpopo, 2013.
Keywords: Etomidate.; Labour induced.